(untitled) (Central Medical College Journal, 2022)
These cases may go unrecognized, and even among those who are known to be hypoxemic, some do not use supplemental oxygen. During air travel in a hypobaric hypoxic environment, compensatory pulmonary mechanisms may be inadequate in patients with lung disease despite normal sea-level oxygen requirements. In addition, compensatory cardiovascular mechanisms may be less effective in some patients who are unable to increase cardiac output. Air travel also presents an increased risk of venous thromboembolism. Each year worldwide, more than 2.75 billion passengers travel by air, 736 million in the United States alone1. One study reports that over an approximately 3-year period, there were 11,920 In-flight medical emergency calls made by airlines to a medical communications Center; this was estimated to represent almost 1 medical emergency for every 600 flights2. Respiratory symptoms accounted for 12% of this in-air emergencies. The development of respiratory symptoms during flight was associated with an increased risk of hospitalization after air travel (odds ratio [OR], 2.13), second only to possible stroke (OR, 3.36). A previous study reported an average of 72 in-flight deaths per year3, from a population representing approximately 50–60% of the total estimated number of worldwide passengers for that period. Of those deaths, 69% occurred in passengers with no known previous medical illness3 as such, a thorough assessment of patients with chronic lung disease and cardiac disease who are contemplating air travel should be performed. Central Medical College Journal Vol 5 No 2 Jul 2021 PP 116-125